مسؤولية مراقب الحسابات في تقويم مخاطر المشروعات الصغيرة والمتوسطة (Journal of Accounting and Financial Studies ( JAFS ), 2009)
There are many characters which belong to small & medium projects, this is not relate to their size only but also to its quality charchcters & the quantities indicators.There is a focus in the ownership, management, Resources beside the limited internal control system. the auditor must put his program according to the project’s circumstance, so auditing the small projects differs than other projects which maybe is less complex and done by limited personsThis research aims to show the responsibility of certified public accountant in evaluation the risks of the small & medium projects through depending the audit- based risk program which develop the useful information.